Duel at Araluen - Flanagan, John (John Anthony) (New York Philomel Books, 2019)
Maddie, Will Treaty's fearless young apprentice, aided by Hal, Thorn, and the rest of the Heron Brotherband, tries to rescue her mother, Princess Cassandra, who is trapped in Castle Araluen.
Keywords: Apprentices -- Juvenile fiction; Adventure stories; Rescues -- Juvenile fiction; Apprentices -- Fiction; Adventure and adventurers -- Fiction; Rescues -- Fiction; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Legends, Myths, Fables / Arthurian; JUVENILE FICTION / Fantasy & Magic; Fantasy fiction